Between hospitality and misoxenia – aftershocks of the migration crisis in Poland - Cekiera, Rafał (Political Preferences, 2017)
Refugee crisis is a major challenge for the whole of Europe the humanitarian, social and political. It affects individual societies both in a direct way, when growth in the number of visitors exceeds the adaptability, and indirectly, through its multidimensional social consequences. In Poland, the refugee crisis can defined as the phantom. Despite the trace number of refugees and the slight number of immigrants, the problem and the way the debate over it cause very significant social repercussions. These repercussions manifest themselves in changes in attitudes with respect to refugees or a more widely-foreign, clearly materialised in the research. Key words: crisis migration, refugees, public debate, hospitality, misoxenia